2018
DOI: 10.1098/rstb.2017.0284
|View full text |Cite
|
Sign up to set email alerts
|

A distributed brain network predicts general intelligence from resting-state human neuroimaging data

Abstract: Individual people differ in their ability to reason, solve problems, think abstractly, plan and learn. A reliable measure of this general ability, also known as intelligence, can be derived from scores across a diverse set of cognitive tasks. There is great interest in understanding the neural underpinnings of individual differences in intelligence, because it is the single best predictor of long-term life success. The most replicated neural correlate of human intelligence to date is total brain volume; howeve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
214
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 272 publications
(237 citation statements)
references
References 104 publications
(141 reference statements)
20
214
3
Order By: Relevance
“…This result highlights a promising future direction for functional MRI predictive analyses because it tentatively suggests that improvements in accuracy may allow the techniques to be used as a proxy for traditional cognitive batteries in combination with birth-related variables (Dubois et al, 2018). This result highlights a promising future direction for functional MRI predictive analyses because it tentatively suggests that improvements in accuracy may allow the techniques to be used as a proxy for traditional cognitive batteries in combination with birth-related variables (Dubois et al, 2018).…”
Section: Clinical and Cognitive Relationships With Brain Signaturesmentioning
confidence: 79%
See 2 more Smart Citations
“…This result highlights a promising future direction for functional MRI predictive analyses because it tentatively suggests that improvements in accuracy may allow the techniques to be used as a proxy for traditional cognitive batteries in combination with birth-related variables (Dubois et al, 2018). This result highlights a promising future direction for functional MRI predictive analyses because it tentatively suggests that improvements in accuracy may allow the techniques to be used as a proxy for traditional cognitive batteries in combination with birth-related variables (Dubois et al, 2018).…”
Section: Clinical and Cognitive Relationships With Brain Signaturesmentioning
confidence: 79%
“…Our further analyses also demonstrated that the prediction of general IQ was improved by the addition of the ALFF decision score. This result highlights a promising future direction for functional MRI predictive analyses because it tentatively suggests that improvements in accuracy may allow the techniques to be used as a proxy for traditional cognitive batteries in combination with birth-related variables (Dubois et al, 2018). Specifically, high prediction error was noted in the high (>110) and low (<90) IQ ranges, thus further research is needed using larger samples to improve predictive capacity (see Data S1).…”
Section: Clinical and Cognitive Relationships With Brain Signaturesmentioning
confidence: 79%
See 1 more Smart Citation
“…Constructing a General Intelligence Factor We conducted an exploratory factor analysis utilizing the approachß and associated code made available by Dubois and colleagues (https://github.com/adolphslab/HCP_MRI-behavior), who recently investigated prediction of intelligence from resting state fMRI in the HCP dataset 58 .…”
Section: 3mentioning
confidence: 99%
“…In prior work, working memory tasks were often used to investigate brain regions implicated in general intelligence 22,24,29 , due to extensive evidence that working memory and intelligence are closely related [53][54][55][56] . In other lines of research, a number of structural and functional imaging studies have highlighted the involvement of FPN and DMN in general intelligence 14,57,58 . Of particular relevance, we recently showed that cognitive tasks that produce greater separation between FPN and DMN activation are more effective for prediction of intelligence 59 .…”
Section: Introductionmentioning
confidence: 99%